EXPLORING THE IMPACT OF QRIS TECHNOLOGY ON GEN Z INTENTION TO CONTRIBUTE INFAQ TO MOSQUES - Arifin, Samsul; Ratnasari, Ririn Tri; Pertiwi, Tanza Dona (Universitas Islam Negeri Mataram, 2024)
This study examines the impact of religiosity, ease of use, motivation, and intention to donate infaq among Generation Z in Jember, Indonesia, focusing on mosque donations via QRIS technology. Using a quantitative approach with 100 participants and analyzed through SEM-PLS, the study finds that religiosity enhances motivation through goal-focused behavior. In contrast, ease of use promotes motivation by simplifying the donation process. The research highlights QRIS's benefits, such as increased convenience and transparency, but also identifies challenges, including low digital literacy and limited understanding of infaq among some congregants. These findings suggest that while QRIS has the potential for improving mosque donations, addressing digital literacy and comprehension barriers is essential for maximizing its effectiveness among younger generations.